Case report: Spontaneous carotid-cavernous fistula associated with persistent primitive trigeminal artery aneurysm rupture - Sun, Peng; Chai, Yuan; Fang, Wei; Chen, Hu; Long, Qianfa; Zhao, Zhenwei; Zhang, Tao (Frontiers in Neurology, 2022)
Background The incidence of carotid cavernous fistula (CCF) associated with persistent primitive trigeminal artery (PPTA) aneurysm rupture is extremely rare. We presented a case about a spontaneous CCF secondary to a ruptured PPTA aneurysm, which was successfully embolized with coils and onyx-18 by a trans-arterial approach. Case presentation A 55-year-old female suffered a sudden onset of headache, left orbital pain, and pulsatile exophthalmos for a month without any history of trauma. Angiography revealed a left-sided CCF associated with a ruptured PPTA aneurysm, with major drainage to the ipsilateral superior ophthalmic vein. Through a trans-arterial approach, the fistula and ruptured PPTA aneurysm were embolized with coils and onyx-18, while the cavernous sinus and PPTA were well-preserved. However, the preserved PPTA vanished at 4 month follow-up. The patient had no neurological deficit from hospitalization to 1 year follow-up period. Conclusion Trans-arterial approach was a reasonable choice for spontaneous CCF associated with ruptured PPTA aneurysm. The requirement for PPTA preservation depended on individual evaluation.